Coral and algal community primary succession on new vertical substrate at Rackham’s Cay, Port Royal, Jamaica - Camilo Trench (Revista de Biología Tropical, 2014)
Jamaica’s trans-shipment industry is amongst the largest in the Caribbean with 90% of trans-shipment activities occurring in Kingston Harbour. The eastern ship channel is populated with patch and fringing coral reefs. In 2002, approximately 20% of an originally sloping face of Rackham’s Cay, on the southern edge of the channel, was cut vertically to 18m and dredged to widen the channel. The successional changes on the newly created vertical limestone wall was assessed between 2009 and 2012 at 5m, 10m and 15m depths using bi-annual photographs of fixed 1 m 2 quadrats. Photographs were analyzed using Coral Point Count. No colonization of either algal or coralline species was observed at 15m. Initially calcareous and fleshy algae dominated at 5m but showed a gradual decrease over time. Calcareous algae dominated at 10m and increaseed gradually over the 4 years. Stony corals at both 5m and 10m had overall low cover and slow colonization; the shallower depth had more coverage (4.1% maximum in 2011). Siderastrea sidera -which dominated Rackham’s Cay before dredging- was consistently present in low coverage. Colonization by species of Acropora and Scolymia indicate slower but better succession at 10m. Ten years following dredging activities, colonization and recruitment have been slow but successful at 5m and 10m; species previously described as abundant lead the colonization. We recommend limiting coral relocation activities to depths not exceeding 10m.